ENDOGENOUS RELATIONSHIP OF ACCIDENT OCCURRENCE WITH SPEED, TRAFFIC HETEROGENEITY AND DRIVING ENVIRONMENT ON INTER-URBAN ROADS IN INDONESIA - Siregar, Martha Leni; Tjahjono, Tri; Nahry (Journal of Applied Engineering Science, 2020)
Speed performances and characteristics of traffic have mostly been considered as homogeneous across vehicles. In countries where the roads are dominated by mixed types of vehicles, the heterogeneity needs to be considered. This study is aimed at modeling how traffic heterogeneity as captured in speed, speed deviation, and traffic volume determines the fatality rates and accident rates. Traffic volume, road geometry (bendiness, hilliness, bend density and hill density) and road surface condition (represented by IRI) become the independent variables in a simultaneous regression using structural equation model (SEM). SEM is adopted to represent the hierarchical causal effects between the independent variables and dependent variables. The data cover inter-urban roads in eight provinces in Indonesia from 2012-2016 and 2019. Speed is not significant in predicting accident rate, and speed deviation is not significant in predicting fatality rate. An increase in speed deviation lowers the accident rates; an increase in speed increases fatality rates. Road geometry and traffic volume negatively impact the speed deviations of all vehicle categories, indicating that when there is more traffic on the road, the speeds of all vehicle categories become more homogenous. Bend density, bendiness, hill density and hilliness negatively affect both the speed and the speed deviations of the vehicles of all categories The findings of the study can contribute to traffic policing and traffic safety improvement schemes for heterogeneous traffic
Keywords: speed, road geometry, IRI, fatality rates, accident rates, hilliness, bendiness, endogeneity, heterogeneous traffic